Nanocellulose based asymmetric composite membrane for the multiple functions in cell encapsulation. (20th February 2017) - Park, Minsung; Shin, Sungchul; Cheng, Jie; Hyun, Jinho
Highlights: The membrane for cell encapsulation was prepared using nanocelluose hydrogels. The permeability of the membrane was controlled by the heterogeneous coating. BC composite membranes showed a superior mechanical property. BC composite membranes were highly cell viable as well as bioactive. Cells encapsulated in the BC composite membrane kit released dopamine to the medium through the membrane. Abstract: We describe the nanocomposite membrane for cell encapsulation using nanocelluose hydrogels. One of the surfaces of bacterial cellulose (BC) pellicles was coated with collagen to enhance cell adhesion and the opposite side of the BC pellicles was coated with alginate to protect transplanted cells from immune rejection by the reduced pore size of the composite membrane. The morphology of nanocomposite membrane was observed by scanning electron microscopy and the permeability of the membrane was estimated by the release test using different molecular weights of polymer solution. The nanocomposite membrane was permeable to small molecules but impermeable to large molecules such as IgG antibodies inferring the potential use in cell implantation. In addition, the BC-based nanocomposite membrane showed a superior mechanical property due to the incorporation of compared with alginate membranes. The cells attached efficiently to the surface of BC composite membranes with a high level of cell viability as well as bioactivity. Cells grown on the BC composite membrane kit released dopamine freely to the medium through the membrane, which showed that the BC composite membrane would be a promising cell encapsulation material in implantation.